2022
DOI: 10.1016/j.conctc.2021.100879
|View full text |Cite
|
Sign up to set email alerts
|

Assessing impacts of redeveloping public housing communities on obesity in low-income minority residents: Rationale, study design, and baseline data from the Watts Neighborhood Health Study

Abstract: Introduction Obesogenic built- and social-environments in low-income and minority communities are often blamed for the higher rates of obesity in this population, but existing evidence is based largely on observational studies. This study leverages a natural experiment created by the redevelopment of a public housing community to examine the impact of major improvements to the housing, built, and social environments on obesity among residents. Methods/design The study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Residing in PRH was not directly associated prolonged sitting. Our results also partly explain the mixed results of previous literature on the association between PRH residence and obesity [ 9 , 12 ]. They were possibly caused by the competition of the two forces, including eating and physical activity behaviors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Residing in PRH was not directly associated prolonged sitting. Our results also partly explain the mixed results of previous literature on the association between PRH residence and obesity [ 9 , 12 ]. They were possibly caused by the competition of the two forces, including eating and physical activity behaviors.…”
Section: Discussionsupporting
confidence: 85%
“…If PRH residence leads to poor health outcomes, the pathways could be related with poor housing and neighborhood environment in PRH. However, a related study, which leveraged a natural experiment created by PRH redevelopment in Los Angeles, found that there was no significant change in weight-related outcomes during the two years of baseline after the improvements to housing and the built and social environments in PRH communities [ 9 ]. Yet, weight-related outcomes, such as body mass index, are relatively long-term health consequences and need to be observed over time.…”
Section: Introductionmentioning
confidence: 99%
“…The staggered implementation of NBS for CF across 44 US states between 2004 and 2009 mimics an observational (nonexperimental) stepped-wedge design. 9 A stepped-wedge design is essentially a 1-way crossover study in which all clusters (in this case, the states) begin observation in a period of nonintervention, followed by a rollout period during which the number of clusters exposed to the intervention increases, and then ends with all clusters exposed to the intervention. In our study, the period 2000 to 2003 was the nonintervention period, 2004 to 2011 was the rollout period, and 2012 to 2018 was the period in which all states were exposed to the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The study recruited adult and child residents from Jordan Downs, and two other public housing communities not undergoing redevelopment (Imperial Courts, Nickerson Gardens) in Watts during 2018–2019. The majority of participants were recruited from Jordan Downs due to study design consideration described elsewhere [ 44 ]. Participants were recruited through a multi-pronged approach collaborating with resident leaders at each site, including distribution of flyers and letters to homes, promotion at onsite events, and door-to-door visits.…”
Section: Methodsmentioning
confidence: 99%
“…Participants also completed body composition measurements conducted by trained study staff. Additional details on the methods of the overall study are presented in another paper [ 44 ].…”
Section: Methodsmentioning
confidence: 99%